The Influence Of Positive E-WOM And Perceived CSR On Purchase Intention Mediated By Brand Attitude In The Retail Industry In Indonesia - Andrian, Uray; Kurniawati, Kurniawati (SEAN Institute, 2024)
This research aims to analyze the influence of perceptions of corporate social responsibility (CSR) on purchasing intentions; This research also tests the mediating effect of Generation Y's attitudes towards brands and the moderating effect of their attitudes towards CSR. By using a hypothesis testing research design. Data was collected using questionnaires to 235 respondents who made purchases at minimarkets and the data was processed using the SEM method